PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN PADA USAHA KECIL DAN MENENGAH (UKM) DI KOTA BATAM - Haldy, Muhammad; Khoiri, M; Kusumawardani, Wulandari (Universitas Putera Batam, 2024)
Direct marketing is very good at focusing strategies to promote specific products and services and contacting consumers to provide clearer information, analyzing characteristics and recording consumer trends. In addition, direct marketing also allows companies to choose the right and specific consumers so that customer loyalty occurs. This study aims to determine the effect of trust, commitment, communication, and conflict management on customer loyalty. This research uses descriptive quantitative method which is causal and comparative. The data were obtained by sharing the google form link with 400 respondents, namely people in Batam City as the research sample. The sampling method used was nonprobability sampling and the determination of the sample used purposive sampling. Furthermore, the data were analyzed using the SPSS version 24 application. Based on a series of statistical test results, it is found that the creation of customer loyalty by paying attention to variables, trust, commitment and communication has a significant positive effect on customer loyalty. Meanwhile, conflict management has no significant effect on customer loyalty.